ESTIMATING THE ECONOMIC LOSSES OF UNUSED MEDICINES IN THE COMMUNITY: A LITERATURE REVIEW OF ECONOMIC LOSSES AND MANAGEMENT EFFORTS IN INDONESIA - Gunawan Widjaja; Diana Laila Ramatillah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Expenditure on medicines is one of the largest components of healthcare costs in Indonesia. However, a proportion of medicines obtained by the community are not used to their full extent, either due to changes in therapy, side effects, non-compliance, or expiry. This phenomenon results in significant economic losses, with an average of 18-32% of the total value of medicines stored in households being unused or expired. Studies in several cities such as Yogyakarta, Kudus, and East Banjarmasin show that the economic value of unused medicines per household ranges from Rp3,348 to Rp13,698, and if extrapolated nationally, the potential loss could reach hundreds of millions of rupiah. In addition to wasting money, unused medicines also increase health risks and environmental pollution. Management efforts that have been made include public education through the DAGUSIBU programme, medicine take-back, as well as strengthening regulations and the role of pharmacists, but their implementation still faces challenges in coverage and effectiveness. Cross-sector collaboration is needed to strengthen education, improve the collection system of leftover medicines, and increase supervision of pharmaceutical waste disposal to reduce economic losses and improve public health.